Education of Geography in Liquid Society - Tonda Monllor, Emilia María; Alcaraz, Rafael Sebastiá (Journal of Geography Education, 2020)
This paper aims to explore Zygmunt Bauman’s concept of liquid society considering its relevance for scholarship in Geography and its consequences for the teaching and learning of Geography as a school subject. Thereby, time and space served as the structuring criteria given their importance for Geography as an academic discipline.The paper follows a Popperian approach contrasting theoretical reflections with spatial reality. Based on these findings, the paper reflects on possible references for teachers to develop their Geography curriculum in changing and uncertain times.